Stress Kerja dan Kualitas Tidur Sebagai Determinan Utama Kelelahan Kerja pada Pekerja Konstruksi - Intan Pardyani; Indri Hapsari Susilowati (FORIKES, 2024)
Fatigue is a concern in the workplace because it has the potential to affect the productivity, health and safety of workers; which is the main cause of accidents and occupational diseases in construction workers. The aim of this scientific study was to determine the determinants of fatigue in construction workers. This study was a literature review, which used the PRISMA protocol. Literature was searched from 2 databases, namely Research Gate and Science Direct, with the keywords